2011
DOI: 10.1007/s11099-011-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between yellow-green and green cultivars of four vegetable species in pigments, ascorbate, photosynthesis, energy dissipation, and photoinhibition

Abstract: Yellow-green foliage cultivars of four vegetables grown outdoors, i.e., Chinese mustard (Brassica rapa), Chinese kale (Brassica oleracea var. alboglabra), sweet potato (Ipomoea batatas) and Chinese amaranth (Amaranthus tricolor), had lower chlorophyll (Chl) (a+b) (29-36% of green cultivars of the same species), total carotenoids (46-62%) and ascorbate (72-90%) contents per leaf area. Furthermore, yellow-green cultivars had smaller photosystem II (PSII) antenna size (65-70%) and lower photosynthetic capacity (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Any environmental and physiological factors resulting in decreased photosynthesis rates at a constant PPFD should be expected to have the potential to lead to a greater excess of absorbed light. It was reported that the leaves with lower Chl content showed a lower photosynthetic rate [6]. Thus, under moderate light intensities, leaves with low Chl content had low p values due to high energy dissipation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Any environmental and physiological factors resulting in decreased photosynthesis rates at a constant PPFD should be expected to have the potential to lead to a greater excess of absorbed light. It was reported that the leaves with lower Chl content showed a lower photosynthetic rate [6]. Thus, under moderate light intensities, leaves with low Chl content had low p values due to high energy dissipation.…”
Section: Discussionmentioning
confidence: 96%
“…The measurements of ChlF and PRI are simple and reliable methods for estimating the photosynthetic rate [4,5]. However, previous research also found that ChlF parameters were affected by the amount of photosynthetic pigments [6]. The effect of pigments on ChlF and PRI in Chinese kale species with different leaf colors subjected todifferent light intensities has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently several ornamental cultivars of sweetpotato having yellow, light-green or variegated green/yellow leaves. Examples of these ornamental cultivars include ‘Margarita’ (Armitage and Garner, 2001), ‘Sweet Caroline Light Green’ (Pecota et al ., 2004b), ‘Sweet Caroline Sweetheart Light Green’ (Yencho et al ., 2008a), ‘Sweet Caroline Green Yellow’ (Yencho and Pecota, 2008b) and ‘CH-1’ (Weng et al ., 2011). However, these ornamental cultivars are not maintained in the USDA-ARS sweetpotato germplasm collection at PGRCU.…”
Section: Discussionmentioning
confidence: 99%
“…The ETR correction factor of 0.84 was used because only a fraction of incident light is actually absorbed by the two PSs (Wong et al 2014). Non-photochemical quenching (NPQ) was calculated as (Fm/Fm') −1 [21]. Moreover, the dark respiration rate of CO 2 (Rd), light quantum yield of CO 2 (Qy), and light compensation point (LCP) were obtained from the linear regression of photosynthetic light response curves to illumination measured from 0~100 µmol PPFD m −2 s −1 [22,23].…”
Section: Methodsmentioning
confidence: 99%